Avesta – Ancient Literary and Historical Monument (Journal of Oriental Studies, 2018)
The article analyses Avesta, the one of the most ancient monuments of Iran. Avesta is an ancientIranian written monument that reached us through religious texts. The text of Avesta consists of 21 booksand 350000 words. For many years Avesta existed only orally. In addition, Avesta provides accurate informationabout the ancient history of Central Asia, and not only about Iran, as well as studies of Kazakhscientists about this sacred book. By the present time, Avesta has been preserved in the following books:Jasna, Visperad, Videptat, Yashta, Malaya Avesta. Avesta is the literary and historical document that is animportant monument for studying antiquity, culture and life, social and political institutions, epic, andother issues of the history and traditions of the tribes and peoples of Central Asia and Iran.